Trade with agri-food products on international markets: opportunities and risks for Moldova - Cimpoies, Liliana; Sarbu, Olga (INCE, 2022)
The aim of this paper is to analyze the trade advantages and/or disadvantages of Moldova’s agricultural and food products on international markets. The paper is based on statistical data analysis regarding agri-food foreign trade by using the aggregations HS 01-24 according to the Combined Nomenclature of Goods. The examined time series refer to 2010-2019. In order to assess the competitiveness of agri-food products on international markets, trade indicators as Trade Balance Index (TBI), Lafay index and Relative Trade Advantages (RTA) were calculated. According to the obtained results, Moldova has trade advantages for some commodities as oil seeds and oleaginous plants, cereals, beverages, edible fruits and nuts, animal or vegetable fats and oils, preparations of vegetables. Scopul lucrării este analiza avantajelor și/sau dezavantajelor comerțului cu produse agroalimentare al Republicii Moldova pe piețele internaționale. Studiul se bazează pe analiza datelor statistice aferente comerțului internaționale pe secțiuni armonizate 01-24 în perioada anilor 2010-2019. Pentru estimarea competitivității produselor agroalimentare au fost utilizați mai mulți indicatori ca Indicele balanței comerciale (IBT), indicele Lafay, indicele avantajelor comerciale relative (RTA) etc. Conform rezultatelor obținute, Republica Moldova are poziții comerciale avantajoase pe piețele globale pentru comerțul cu semințe și fructe oleaginoase, cereale, băuturi, fructe comestibile și nuci, grăsimi și uleiuri de origine vegetală, preparate din legume și fructe etc.
Comerțul cu produse agroalimentare pe piețele internaționale: oportunități și riscuri pentru Republica Moldova
Text: lb. rom. Abstract în lb. engl., rom. Referinţe bibliografice: p. 329 (11 titl.). JEL Classification: Q17, F10.
Keywords: trade; competitiveness; agri-food products; comert; competitivitate; produse agroalimentare